Improving Students Vocabulary Through Blindfold Games - Tauricha Astiyandha; Lisa Muchlisoh (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2019)
This study aims to identify the extent to which student knowledge in understanding vocabulary using blindfold games. By using blindfold games, students are expected to understand more in using vocabulary. Blindfold is the method students use about things in class. After teaching vocabulary to students, both writing and pronunciation, to practice descriptions, we can use the blindfold game. Before entering the game, it would be better if students run simple description phrases. Enter the game, students as usual describe them with cloth or sketches that have been prepared. After all students are closed, the teacher will provide ready things like books, pencils and pens. Students are given to describe these objects. Students who successfully describe and guess correctly. This is done to find out how students cope with vocabulary. The research design of the study was classroom action research. In this research, there were four phrases, plan, action, observe, reflection. This research will be conducted by two cycles to analyze data. The research investigated the eight grade students vocabulary of MtsN 31 Jakarta Timur which was started in August 10, 2018 and ended in September 14, 2018. Researchers collect data by teaching them about vocabulary using bliindfold games and documenting. Data comes from test results and lesson plans. Data collection method is observation. this research was conducted at MtsN 31 Jakarta with 34 participants. This study was successful because there was a significant increase in the first cycle with an average of 61 and the second with an average of 70. This study helped students improve vocabulary.